Wind force coefficients on hexagonal free form shell. (15th January 2015) - Vizotto, Isaias; Ferreira, Antônio Mário
Highlights: Wind pressure effects on a scale model of hexagonal free form shell. Computational and experimental generation of a hexagonal free form shell model. Complete construction of a shell scale model in fiberglass by a CAD/CAM system. Wind pressure on hexagonal free form shell by wind tunnel experiments. Computational fluid dynamics analysis of the wind pressure on free form shell. Abstract: This paper presents the wind force coefficients on non-conventional building of the free form shell structure generated by the simulation of a membrane initially in the horizontal plane surface with hexagonal plant, under the action of self-weight and supported on six corners. Initially is presented the computational model for free form shells generation, the model generated and the correspondent construction of the hexagonal free form shell scale model in fiberglass by a CAD/CAM system. Following is presented the wind tunnel of atmospheric boundary layer and the scale model used to perform the tests to obtain the wind force coefficients. Finally are presented the numerical analysis of the scale model of free form shell structure by the computational fluid dynamics software ANSYS-CFX. The wind force coefficients for the free form shell obtained by the wind tunnel tests and ANSYS-CFX software are compared. The results demonstrates the possibilities to apply the computational fluid dynamic analysis for future applications to analyze other free form shells in order to obtain wind force coefficients.